PEMBELAJARAN SENI GERAK DAN TARI DI RA AL HANIF - Iis Rosidah; Juni Hati Hangoluan Siregar; Nurtia Sumarni Hasibuan; Hilda Zahra Lubis (JURNAL ILMIAH NUSANTARA, 2025)
PAUD is an education designed with the aim of facilitating the growth and development of children as a whole or emphasizing the development of the child's entire personality. This early age of development is a sensitivity phase where children receive influences and efforts to explore their potential, interests, and talents. Children at this age have uniqueness and characteristics that are inherent in them, different from adults. They tend to be interested in activities that involve movement, rhythm, and singing. In particular, early childhood enjoys arts such as dance and music. To introduce dance to them, an educator who is an expert in this field is needed. Learning dance for early childhood includes simple movements and is in accordance with the type of music so that it is easy to understand. Through this learning, children can express themselves more freely, increase their self-confidence, and showcase their abilities. In the context of art, especially in this study, dance expands development not only in the physical aspects of children's motor skills and creativity, but also summarizes various other areas such as cognitive, language, and social-emotional aspects.This study uses observation and interview methods on the application of dance arts at RA Al-Hanif.